The Effectiveness Of The Overseas Internship Program For Workers At The Department Of Manpower And Transmigration Of Bengkulu Province - Shintia, Anisa; Yusuarsono, Yusuarsono; Rikardo, Yanuar (Utami Publisher, 2025)
This study aims to determine the effectiveness of the overseas internship program for workers at the Department of Manpower and Transmigration of Bengkulu Province. Using a qualitative approach, data were collected through interviews and documentation involving five informants, including three key informants and two supporting ones. The analysis applies Cambel J.P.'s effectiveness theory, which includes five key indicators: program success, target achievement, satisfaction, input-output ratio, and overall goal fulfillment. The findings reveal that the program operates in line with its intended objectives, though it faces several challenges such as a demanding selection process and limited outreach to the public. Most of the program's targets are achieved, although the input-output efficiency remains relatively low. Participant satisfaction also requires improvement, particularly regarding access to information and supporting infrastructure. Overall, the program is considered moderately effective in enhancing workforce competence and competitiveness, though further evaluation is necessary to improve its impact and efficiency.